Malay Traditional Folk Songs In Ulu Tembeling: Its Potential For A Comprehensive Study - Chan, Cheong Jan (Universiti Putra Malaysia Press, 1998)
The aim of this research is to discover the potential of music in Ulu Tembeling for a comprehensive study, as well as to increase the repertoire of Malay songs for music education purposes. A fieldwork had been carried out in the five main villages in Ulu Tembeling where the songs of the villagers were recorded as many as possible. The sound data had been transcribed to notation and analyzed. Around ten types of songs were found in Ulu Tembeling. Among them are: Indung; Saba; Lagu Dodoi; Lagu Bercerita; Lagu Permainan; songs for Tarian Lukah,Tarian Mayang, Tarian Limbung; and Dikir Rebana. The analysis showed the variety of tunes and they have specific characteristics, such as asymmetrical time, the flexibility between down beat and up beat, etc. The result demonstrated that there were more repertoires of Malay melodies, and the original musical characteristics of Malay music may be different from those well known in the urban society. The conclusion of the research is that there is a need to document and study the traditional folk songs of Ulu Tembeling comprehensively.